2019
DOI: 10.1038/s41598-019-56148-w
|View full text |Cite
|
Sign up to set email alerts
|

PtomtAPX, a mitochondrial ascorbate peroxidase, plays an important role in maintaining the redox balance of Populus tomentosa Carr

Abstract: Plant mitochondria are important energy-producing structure and ROS are generated as byproducts. APX is one enzyme of the AsA-GSH cycle to reduces H2O2 to water. We identified both PtomtAPX and PtosAPX are located in mitochondria of Populus tomentosa Carr. PtomtAPX is specifically targeted to mitochondria, while PtosAPX is dual targeted to both chloroplast and mitochondria. The expression of PtomtAPX in mitochondria was 60-fold that of PtosAPX by ELISA and qPCR analysis. Under high light stress, the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
2
11
1
Order By: Relevance
“…Previous studies have identified seven APX genes in Populus trichocarpa [53], In this study, 11 PtrAPX genes have been identified encoding seven cytosolic isoforms, and four chloroplastic isoforms. Among the PtrAPXs genes located in chloroplast, PtrAPX1 and PtrAPX5 are dual-targeted to chloroplasts and/or mitochondria, consistent with the findings that PtosAPX and AtsAPX are dual-targeted to these two organelles [9,30].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies have identified seven APX genes in Populus trichocarpa [53], In this study, 11 PtrAPX genes have been identified encoding seven cytosolic isoforms, and four chloroplastic isoforms. Among the PtrAPXs genes located in chloroplast, PtrAPX1 and PtrAPX5 are dual-targeted to chloroplasts and/or mitochondria, consistent with the findings that PtosAPX and AtsAPX are dual-targeted to these two organelles [9,30].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, PtrAPX1 located in chloroplasts and/or mitochondria was stongly induced by high salinity in leaves (Figure 9). A previous study showed that PtomtAPX is dual targeted to both chloroplast and mitochondria of Populus tomentosa Carr, and showed the same expression pattern under salt stress [30]. Based on the present phylogenetic reconstruction (Figure 1), cytosolic PtrAPX6 is homologous to OsAPX2, and the relative expression level or PtrAPX6 in roots was increased approximately 16-fold at 3 and 6 h under salt stress.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Using AsA as a substrate, the activity of the enzyme PtotAPX was measured under different concentration gradients of other substrates. Compared to the results shown by Yin et al [ 28 ], PtotAPX has a greater affinity for AsA ( Table 1 ). Taken together, these results indicate that PtotAPX could utilize lower concentrations of AsA to scavenge H 2 O 2 .…”
Section: Discussioncontrasting
confidence: 67%
“…On the other hand, mitochondria are also an important site for reactive oxygen species (ROS) synthesis [58][59][60]. positively correlated with xylem lignification [22] and cellulose accumulation in plants growing in salt stress conditions [61].…”
Section: An Increase In the Number Of Mitochondria Acceleratesmentioning
confidence: 99%